2018
DOI: 10.2340/00015555-2794
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Severe Recalcitrant Hidradenitis Suppurativa with the Interleukin-17A Antibody Secukinumab

Abstract: Fig. 1. Rapid clinical response of hidradenitis suppurativa (HS) to secukinumab treatment. Clinical images of the genital and gluteal region (A) before and (B) after 8 weeks of treatment with the interleukin-17A antibody secukinumab, demonstrating rapid reduction in inflammatory nodules and signs of cutaneous inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 7 publications
1
25
0
3
Order By: Relevance
“…Evidence is lacking for other biologic therapies, and any clinical decisions should be based on close monitoring and risk: benefit assessments (66). Recent studies showed administration of other biologics such as other TNF-alpha blockers (66, [90][91][92], ustekinumab, (93-96) secukinumab, (97,98) bimekizumab, (99) canakinumab, (3, 100) apremilast, (1,101) anakinra, (102) guselkumab (103,104), and rituximab (105) in management of HS.…”
Section: Administration Of Biologics In Hsmentioning
confidence: 99%
“…Evidence is lacking for other biologic therapies, and any clinical decisions should be based on close monitoring and risk: benefit assessments (66). Recent studies showed administration of other biologics such as other TNF-alpha blockers (66, [90][91][92], ustekinumab, (93-96) secukinumab, (97,98) bimekizumab, (99) canakinumab, (3, 100) apremilast, (1,101) anakinra, (102) guselkumab (103,104), and rituximab (105) in management of HS.…”
Section: Administration Of Biologics In Hsmentioning
confidence: 99%
“…Of the IL‐17 neutralizing monoclonal antibodies seculinumab, ixekuzumab and brodalumab, only seculinumab has been approved for the treatment of psoriasis and psoriatic arthritis . It has recently been reported that HS exhibits a clinical response to seculinumab . Current therapeutic efforts focus on attenuating IL‐17 signalling in HS …”
Section: Therapeutic Agents Affect the T Helper 17 Cell/regulatory T‐mentioning
confidence: 99%
“…[217][218][219] It has recently been reported that HS exhibits a clinical response to seculinumab. 220,221 Current therapeutic efforts focus on attenuating IL-17 signalling in HS. 133,222,223…”
Section: Biologicsmentioning
confidence: 99%
“…102 Successful treatment of severe recalcitrant hidradenitis suppurativa with the interleukin-17a antibody secukinumab was recently reported. 103 A successful response was also reported with the monoclonal antibody anti-CD20 rituximab (two courses of 200 mg) in a patient with idiopathic carpotarsal osteolysis and chronic active antibody-mediated rejection. 104 Investigations are currently ongoing or recruiting for diverse biologic agents, such as CJM112 (a fully human anti-IL-17A mAb [NCT02421172]) and MABp1 (human anti-IL-1a antibody in patients with HS refractory to adalimumab [NCT02643654]).…”
Section: -Biologic Agentsmentioning
confidence: 93%